Scaling Into the Future With Smartlinks - Bengtson, Jason A. (My University, 2014)
The mobile revolution has changed the digital landscape in profound ways and it can be a struggle to keep up. A proliferation of websites have sprung up designed around the special needs of mobile devices; needs which include small screens, touch interaction, and limited bandwidth and processing power. By far the most commonly seen solution is for organizations or individuals seeking to be "mobile friendly" to create a "mobile site" mirroring their regular website. These mobile sites often showcase resources and features that would (or so the designers believe) be of particular interest to mobile users, packaged in Web design built around mobile device features. A persistent challenge is getting visitors to those sites, as anyone who has read my article about mobile redirect scripts knows. The approach to mobile, however, is evolving.
Citation: Bengtson, Jason. "Scaling Into the Future with Smart Links." Journal of Hospital Librarianship 12.4 (2012) : 378-383. Print